2011
DOI: 10.1007/s10531-011-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Can early loss of affiliates explain the coextinction paradox? An example from Acacia-inhabiting psyllids (Hemiptera: Psylloidea)

Abstract: Recent models indicate that coextinction events should be numerous but empirical support for coextinction is paradoxically scarce. I investigated whether the coextinction paradox is due to affiliates becoming extinct well ahead of their hosts, with the disjunction masking the coextinction event. Using psyllids (Hemiptera: Psylloidea) on acacias (Mimosaceae: Acacia) in southern Sydney as an example system, I compared the density of affiliate species and the proportion of specialists on threatened versus secure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This result supports coextinction theory; however, the proportion of specialist parasites was not significantly different, suggesting that host declines lead to the loss of both specialist and generalist parasites. A similar result was found among acacias and the phytophagous insects that feed on them (Powell ). A recent study of fish parasites found that specialist parasites tend to use hosts with low vulnerability to extinction (Strona, Galli & Fattorini ), which may be additional support for the loss of specialist parasites from threatened hosts.…”
Section: Introductionsupporting
confidence: 77%
“…This result supports coextinction theory; however, the proportion of specialist parasites was not significantly different, suggesting that host declines lead to the loss of both specialist and generalist parasites. A similar result was found among acacias and the phytophagous insects that feed on them (Powell ). A recent study of fish parasites found that specialist parasites tend to use hosts with low vulnerability to extinction (Strona, Galli & Fattorini ), which may be additional support for the loss of specialist parasites from threatened hosts.…”
Section: Introductionsupporting
confidence: 77%
“…We predict that several parasites are at risk of extinction either during the decline of the host or during the conservation efforts to recover the host. [30,31]. These data indicate that factors other than host specificity may also be important determinants of extinction risk for parasites.…”
Section: Trepar 1686 1-11mentioning
confidence: 79%
“…The ectoparasites' dependence on avian hosts implies that they are also coendangered and risk going extinct together with them. In addition, sustained parasite transmission requires a threshold host population size, meaning that some of Darwin's finch ectoparasite species might be already extinct, as parasite extinction could precede that of the hosts (Gompper & Williams, 1998;Altizer et al, 2007;Powell, 2011;Bush et al, 2013;R osza & Vas, 2015). The coextinction threat of a host-parasite system should be assessed on a case by case basis (G omez & Nichols, 2013) as it will depend on the host and the parasite ecology, phylogeny, and the parasite's host range and life cycle (G omez et al, 2012).…”
Section: Darwin's Finches: Ectoparasitesmentioning
confidence: 99%